2021
DOI: 10.1590/1678-7757-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

Impact event and orofacial pain amid the COVID-19 pandemic in Brazil: a cross-sectional epidemiological study

Abstract: Impact event and orofacial pain amid the COVID-19 pandemic in Brazil: a cross-sectional epidemiological study Objectives: This study aims to assess the impact of social isolation, due to the Covid-19 pandemic, on mental health, Temporomandibular Disorder (TMD) and orofacial pain in men and women. Methodology: Individuals living in Brazil answered an online questionnaire on their sociodemographic and behavioral aspects, emotional scale (DASS-21), Impact of Event Scale, and Pain Screener in Temporomandibular Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…For instance, a study conducted during the pandemic in Israeli and Polish indicated that COVID-19-related mental disorders led to the intensification of bruxism and TMD symptoms, and consequently OFP increased (38). Gender differences has been proven to be an influential factor contributed to such processes: the anxiety and stress caused by COVID-19 participate in deteriorating stomatognathic diseases, and women were generally more influential than men (36,39). The crosssectional study from Wuhan lockdown showed a significantly higher impact of COVID-related stress in TMD patients in comparison to orthodontic patients and control population (40).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted during the pandemic in Israeli and Polish indicated that COVID-19-related mental disorders led to the intensification of bruxism and TMD symptoms, and consequently OFP increased (38). Gender differences has been proven to be an influential factor contributed to such processes: the anxiety and stress caused by COVID-19 participate in deteriorating stomatognathic diseases, and women were generally more influential than men (36,39). The crosssectional study from Wuhan lockdown showed a significantly higher impact of COVID-related stress in TMD patients in comparison to orthodontic patients and control population (40).…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, após realização de um refi namento buscando apenas estudos que apresentem prevalências de sintomas de depressão, ansiedade, estresse e sofrimento, excluindo preprints e duplicatas, obtém-se 29 estudos 1 que apresentam um panorama global do acometimento dos brasileiros e apontam para uma alta prevalência de sintomas. Esses estudos apresentam dados do primeiro ano pandêmico (Apêndice B) e representam um ponto de partida importante para discussão e refl exão em relação à saúde mental e prevenção da instalação de transtornos que poderão vir a confi gurar uma 1 Adinolfi et al, 2021;Antonelli-Ponti et al, 2020;Barros et al, 2020;Brunoni et al, 2021;Camargo et al, 2021;Campos et al, 2020;Caxias et al, 2021;Christofaro et al, 2021;D. C. S. Ferreira et al, 2020;F.…”
Section: Experiencia Con Covid-19 Y Síntomas Relacionados Con La Salu...unclassified
“…Влияние социальной изоляции из-за пандемии COVID-19 на психическое здоровье, расстройства ВНЧС и ОФБ изучалось в бразильском исследовании [21]…”
Section: височно-нижнечелюстные расстройства: боль в височно-нижнечел...unclassified